The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jcmm.14399
|View full text |Cite
|
Sign up to set email alerts
|

Targeting miR‐193a‐AML1‐ETO‐β‐catenin axis by melatonin suppresses the self‐renewal of leukaemia stem cells in leukaemia with t (8;21) translocation

Abstract: AML1‐ETO, the most common fusion oncoprotein by t (8;21) in acute myeloid leukaemia (AML), enhances hematopoietic self‐renewal and leukemogenesis. However, currently no specific therapies have been reported for t (8;21) AML patients as AML1‐ETO is still intractable as a pharmacological target. For this purpose, leukaemia cells and AML1‐ETO‐induced murine leukaemia model were used to investigate the degradation of AML1‐ETO by melatonin (MLT), synthesized and secreted by the pineal gland. MLT remarkedly decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The ribosome is a complex molecular machine responsible for protein synthesis in every living cell; additionally, ribosome biogenesis is the machinery that performs protein synthesis. Here we found that cabozantinib inhibited phosphorylation of p70S6K and 4E-BP1, and reduced the protein synthesis of AML1-ETO without increasing its degradation, unlike several anticancer agents that facilitate proteasomal degradation of AML1-ETO oncoprotein [ 38 40 ]. In addition, we clearly excluded the possibility that AML1-ETO dysregulation could be attributed to the cabozantinib-mediated acceleration of the turnover rate by using protein synthesis inhibitor CHX.…”
Section: Discussionmentioning
confidence: 97%
“…The ribosome is a complex molecular machine responsible for protein synthesis in every living cell; additionally, ribosome biogenesis is the machinery that performs protein synthesis. Here we found that cabozantinib inhibited phosphorylation of p70S6K and 4E-BP1, and reduced the protein synthesis of AML1-ETO without increasing its degradation, unlike several anticancer agents that facilitate proteasomal degradation of AML1-ETO oncoprotein [ 38 40 ]. In addition, we clearly excluded the possibility that AML1-ETO dysregulation could be attributed to the cabozantinib-mediated acceleration of the turnover rate by using protein synthesis inhibitor CHX.…”
Section: Discussionmentioning
confidence: 97%
“…MicroRNAs, which are natural inhibitors of multiple genes, are attractive therapeutic molecules provided they are exclusively tumor-suppressive or oncogenic. MiR-193a has been reported to be tumor-suppressive in multiple cancers by downregulating several oncogenic targets [45][46][47][48]. Hence it is potentially a good therapeutic small molecule.…”
Section: Discussionmentioning
confidence: 99%
“…In these cells, melatonin was shown to downregulate Sox9, i.e., a factor that induces various osteoblast-typical genes, and to inhibit proliferation [241]. In leukemia stem cells, inhibition of proliferating self-renewal by melatonin was reported to be mediated by upregulation of miR-193a, which targets AML1-ETO, an oncogenic fusion gene formed by translocation, whose protein is known to increase β-catenin levels [242].…”
Section: Some Aspects Concerning Cancer Stem Cellsmentioning
confidence: 99%